Differential modulation in metabolites revealed with the improvement in the shelf-life of alphonso fruits - Dar, M. Saleem; Dholakia, Bhushan B.; Shanmugam, Haripriya; Gupta, Vidya S.; Subramanian, K. S.; Subramanian, J.; Giri, Ashok P. (Molecular Biotechnology, 2020)
Globally farmers have difficulty in extending the shelf-life of the tropical fruits due to their perishable nature. The present study aimed to assess the effect of hexanal nano-formulation treatment (NFT) on the shelf-life of Alphonso mango. Further, volatilomics was performed to explore the molecular basis of such effect. Untreated and treated fruits were sampled starting from 5th to 21st day after NFT at an interval of 4 days. Moderate changes in visual and digital colour parameters were evident from the intact and dissected fruits of NFT set compared to untreated fruits. Biochemical assays affirmed the phenotypic differences with significant changes in the colour imparting compounds like carotenoids and anthocyanins among them. Further, gas chromatography-mass spectrometry analysis revealed significant qualitative and quantitative variations in the different classes of compounds like lactones, furanones, esters, aldehydes and alcohols. Some of the key metabolites showed differential modulations among the NFT and untreated fruit sets indicating their potential role in various processes, which ultimately might have resulted in delayed ripening of the mango. Overall, this study has demonstrated the beneficial effect of hexanal and identified important metabolites with the enhanced shelf-life in Alphonso that could be useful for farmers and mango-based food/flavour industries.
Keywords: Alphonso; GC-MS; Metabolites; Nano-biotechnology; Nano-formulation; Shelf-life; Volatilomics